Metabolic Peculiarities of Paracoccidioides brasiliensis Dimorphism as Demonstrated by iTRAQ Labeling Proteomics - Araújo, Danielle Silva; Pereira, Maristela; Portis, Igor Godinho; dos Santos Junior, Agenor de Castro Moreira; Fontes, Wagner; de Sousa, Marcelo Valle; Assunção, Leandro do Prado; Baeza, Lilian Cristiane; Bailão, Alexandre Mello; Ricart, Carlos André Ornelas; Brock, Matthias; Soares, Célia Maria de Almeida (Frontiers in Microbiology, 2019)
Paracoccidioidomycosis (PCM), a systemic mycosis with a high incidence in Latin America, is caused by thermodimorphic fungi of the Paracoccidioides genus. The contact with host occurs by the inhalation of conidia or mycelial propagules which once reaching the pulmonary alveoli differentiate into yeast cells. This transition process is vital in the pathogenesis of PCM allowing the fungus survival in the host. Thus, the present work performed a comparative proteome analysis of mycelia, mycelia-to-yeast transition, and yeast cells of Paracoccidioides brasiliensis. For that, tryptic peptides were labeled with iTRAQ and identified by LC–MS/MS and computational data analysis, which allowed the identification of 312 proteins differentially expressed in different morphological stages. Data showed that P. brasiliensis yeast cells preferentially employ aerobic beta-oxidation and the tricarboxylic acid cycle accompanied by oxidative phosphorylation for ATP production, in comparison to mycelia and the transition from mycelia-to-yeast cells. Furthermore, yeast cells show a metabolic reprogramming in amino acid metabolism and in the induction of virulence determinants and heat shock proteins allowing adaptation to environmental conditions during the increase of the temperature. In opposite of that, the alcoholic fermentation found to P. lutzii, at least under laboratory conditions, is strongly favored in mycelium compared to yeast cells. Thereby, the data strongly support substantial metabolic differences among members of the Paracoccidioides complex, when comparing the saprobiotic mycelia and the yeast parasitic phases.